EFEK EKSTRAK ETANOL RIMPANG TEMULAWAK (Curcuma xanthorrhiza Roxb) TERHADAP MEMORI SPASIAL TIKUS MODEL DEMENSIA YANG DIINDUKSI TRIMETHYLTIN - Nuroh Aspamufita; Sapto Yuliani (Universitas Ahmad Dahlan, 2013)
Curcuma xanthorrhiza Roxb is one of the plants containing curcumin. Curcumin has anti-amyloidogenic,antioxidant, and anti-inflammatory activity that can prevent dementia. The aim of the research was to know theeffect of Curcuma xanthorrhiza Roxb rhizome ethanol extract (CREE) to spatial memory on dementia model ratinduced by trimethyltin (TMT). This research use 30 rats, divided into 6 groups, each group consisted of 5 rats. Allgroupswere given trimethyltin intraperitoneal lyexcep tgroup I.Group I (healthy controls) and group II (TMT/illness control) were given a solution of 1% CMC-Na orally. Group III (drug control) were given citicoline 200mg/kgBW orally. Group IV, V, and VI were given CREE orally dose 50 mg/kgBW, 100 mg/kgBW, and 150mg/kgBW respectively. Data of spatial memory were obtained by Morris water maze test consisted of acquisitiontrial, and a probe trial. Data from the test then statistically analyzed by one-way repeated measure ANOVA.Morris water maze test showed that there were significant differences (p<0,05) between TMT group comparedwith CREE dose 50 mg/kgBW, 100 mg/kgBW, and 150 mg/kgBW group. But there was no significant difference(p>0,05) between CREE dose100 mg/kgBW group anddrug control group.Based on the research results can beconcluded that ethanol extract Curcuma xanthorrhiza Roxb rhizome at dose of 100 mg/kgBW can improvespatial memory on dementia model rat induced by trimethyltin.